Structural Analysis and Improvement Design of Brake Pressure Valve Feedback Stage in Multivalve Parallel Brake System - Zhi-peng Huang; Bin Yu; Yun-he Wang; Qi-wei Zhang; Yan Xie; Zuo-jian Xie; Xiang-dong Kong (Shock and Vibration)
The wheel brake device is one of the most widely used landing deceleration devices in modern aircraft. For large aircraft, a multivalve parallel brake system is usually used. When a brake pressure servo valve of a certain type of aircraft is debugged, the output brake pressure of the system shows obvious periodic oscillation with constant amplitude. This paper focuses on the brake pressure servo valve, which is the key component of the system. There are a large number of feedback and adjustment segments in the brake pressure servo valve, which can not only improve the control accuracy but also introduce nonlinear factors to cause system vibration. Therefore, in this paper, the feedback stage structure of the brake pressure servo valve is analyzed and improved, and a new two-stage pressure servo valve is designed to restrain the output brake pressure vibration of the system. Firstly, the structure principle of the original pressure servo valve is defined, and the function of the feedback stage is analyzed. Secondly, in view of the vibration problem caused by the original brake pressure servo valve, a new two-stage brake pressure servo valve is designed, which is the main contribution of this paper. Thirdly, the dynamics model of the proposed two-stage brake pressure servo valve is established, and the simulation model of the brake pressure servo valve-controlled cylinder system and the multivalve parallel brake servo control system is built. Finally, experiments are carried out on the experimental platform of a multivalve parallel brake system to verify that the proposed two-stage pressure servo valve can restrain the vibration of the system more effectively than the original brake pressure servo valve. And the two-stage pressure servo valve prototype is successfully applied to the actual aircraft brake control system; the system can better maintain a stable brake pressure output.